The voluntary intake and digestibility of diets containing different proportions of tef (Eragrostis tef) straw and Trifolium tembense hay when fed to sheep - Mosi, A.K.; Butterworth, M.H. (1985)
An experiment conducted to assess the difference in nutritive value when trifolium hay was fed to sheep at increasing levels with tef straw (Eragrostis tef). Includes data on the composition of the trifolium hay & tef straw on dry matter basis and intake & digestibility of diets containing different proportions of trifolium hay and tef straw fed to sheep.